Perancangan E-magazine sebagai Media Informasi Digital Kampung Saporkren Raja Ampat - Cholimatus Sa'diah; Wahyuniar Pamungkas; Atikah Nurhayati; Fanny Kristiandhi; Lintang Permata Sari Yuliadi (TOBA: Journal of Tourism, Hospitality, and Destination, 2025)
This study aims to design a digital information medium in the form of an e-magazine that serves to document and promote the potential of Saporkren Village in Raja Ampat Regency more broadly and attractively. The research employed a Research and Development (R&D) approach using the ADDIE development model, which consists of five stages: Analyze, Design, Development, Implementation, and Evaluation. The analysis stage was conducted to identify information needs, target audiences, content to be presented, and analysis of similar media. The results indicated that Saporkren Village requires a digital medium capable of systematically showcasing its marine tourism, cultural, culinary, and village profile potentials. The design stage produced an e-magazine structure consisting of a cover, introduction, table of contents, main content, and closing section. During the development stage, the product was evaluated by practitioners experienced in tourism and digital media design, resulting in feasibility percentages of 87.5% (very good category) and 71.4% (good category), respectively. Subsequently, a trial was conducted involving 35 respondents who met the criteria of never having visited Saporkren Village, aged 17–35 years, with a minimum education level of senior high school (or equivalent), and familiar with internet and digital media use. The trial results showed an average percentage score of 95.71%, categorized as very good. Based on the assessments from practitioners and trial participants, the e-magazine was declared feasible to be used as a digital information medium for Saporkren Village. This medium is expected to serve as a reference for local managers in developing digital information content and for the Raja Ampat Tourism Office in creating similar media as part of the digitalization efforts for other tourism villages.